Supporting IP QoS in the General Packet Radio Service. - Priggouris, G. (IEEE Network : the magazine of global information exchange)
The General Packet Radio Service is the current enhancement in the GSM infrastructure, capable of handling Internet protocol traffic for mobile computing and communications. A major deficiency of the current GPRS specification is the lack of adequate IP quality of service support. Two schemes for enhancing the GPRS architecture with the existing IP QoS support architectures, IntServ and DiffServ, are proposed. Solutions are proposed to the problem of establishing QoS reservations across the GPRS core network, and the required signaling enhancements and modifications in the components of the GPRS architecture are identified. Of the two proposed schemes the IntServ one requires frequent refreshing of state information and extra signaling. To quantify the effect that signaling overhead has on GPRS operation and performance, a simulation model of the proposed IntServ architecture was developed, which includes models of the GPRS cellular infrastructure, network traffic, and user movement. The obtained simulation results show that the proposed IntServ architecture demonstrated good scalability, even for large user populations